Hsp90 is important for fecundity, longevity, and buffering of cryptic deleterious variation in wild fly populations. - Chen, B.; Wagner, A. (BMC Evolutionary Biology, 2012)
In the laboratory, the Drosophila melanogaster heat shock protein Hsp90 can buffer the phenotypic effects of genetic variation. Laboratory experiments either manipulate Hsp90 activity pharmacologically, or they induce mutations with strong effects in the gene Hsp83, the single-copy fly gene encoding Hsp90. It is unknown whether observations from such laboratory experiments are relevant in the wild.We here study naturally occurring mutations in Hsp83, and their effects on fitness and phenotypic buffering in flies derived from wild populations. We examined more than 4500 flies from 42 Drosophila populations distributed world-wide for insertions or deletions of mobile DNA in or near the Hsp83 gene. The insertions we observed occur at low population frequencies, and reduce Hsp83 gene expression. In competition experiments, mutant flies performed much more poorly than wild-type flies. Mutant flies were also significantly less fecund and shorter-lived than wild-type flies, as well as less well buffered against cryptic deleterious variation, as we show through inbreeding experiments. Specifically, in Hsp83 mutant flies female fecundity dropped to much lower levels after inbreeding than in wild-type flies. At even slightly elevated temperatures, inbred mutant Hsp83 populations went extinct, whereas inbred wild-type populations persisted.Our work shows that Hsp90, a regulator of the stress response and of signaling, helps buffer deleterious variation in fruit flies derived from wild population, and that its buffering role becomes even more important under heat stress.